Pengaruh Person Job Fit, Person Organization Fit Terhadap Komitmen Organisasi dengan Job Satisfaction sebagai Variabel Intervening: Studi pada Karyawan Non PNS Kantor Samsat Kebumen - Rizqi Anggraheni Rasito Putri; Parmin Parmin (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2022)
This study aims to analyze the level of commitment of non-civil servant employees at the Kebumen Samsat Office. This study uses the variables Person Job Fit and Person Organization Fit to analyze the effect of Non-PNS Employee Organizational Commitment. In addition, this study uses the Job Satisfaction variable as an intervening variable to analyze the effect of Person Job Fit, Person Organization Fit on Organizational Commitment of Non-PNS employees at the Kebumen Samsat Office. The population in this study were non-civil servants at the Kebumen Samsat Office, amounting to 39 people. The sampling technique used is a saturated sample so that the entire population is used as a sample. Data collection techniques using a questionnaire. Data analysis used is validity test, reliable test, classic assumption test, hypothesis test, correlation analysis, Sobel test and path analysis. Data processing tools using SPPS 25.0 for windows. The results of this study indicate that Person Job Fit has a positive and significant effect on Job Satisfaction. Person Organization Fit does not directly affect Job Satisfaction. Person Job Fit has a positive and significant effect on Organizational Commitment. Person Organization Fit has a positive and significant effect on Organizational Commitment. Job Satisfaction has a positive and significant effect on Organizational Commitment. Job Satisfaction can mediate the influence of Person Job Fit on organizational commitment. Job Satisfaction can mediate the influence of Person Organization Fit on Organizational Commitment.